Dermoscopy of disorders of hypopigmentation - Yasmeen Jabeen Bhat; Soumil Khare; Nahida Nabi (Wolters Kluwer Medknow Publications, 2022)
Dermoscopy has traditionally been used to diagnose neoplasms and, more recently, to evaluate inflammatory conditions. Recent observational studies have suggested a role for dermoscopy in identifying and differentiating various hypopigmentary disorders. This comprehensive review will summarize the growing literature on the use of dermoscopy for hypopigmentary disorders.